The low-luminosity galaxy population in the NGC 5044 group - Cellone, Sergio Aldo (2005)
We present multicolour imaging for a sample of 33 dwarf and intermediate-luminosity galaxies in the field of the NGC 5044 Group, complemented with mid-resolution spectroscopy for a subsample of 13 objects. With these data, a revised membership and morphological classification is made for the galaxies in the sample. We were able to confirm all but one of the 'definite members' included in the spectroscopic subsample, galaxies which were originally classified based on morphological criteria. An important fraction of background galaxies, however, is probably present among 'likely' and 'possible' members. The presence of a nucleus could be detected in just five out of the nine galaxies originally classified as dE,N, confirming the intrinsic difficulty of photographic-plate morphological classification for this kind of object. Our deep surface photometry provided clear evidence for disc structure in at least three galaxies previously catalogued as dE or dS0. Their transition-type properties are also evident from the colour-magnitude diagram, where they lie near the late-type galaxy locus, suggesting an evolutionary connection between a parent disc-galaxy population and at least some present-day dEs. Six new dSph candidates were also found, most of them at small projected distances from NGC 5044, the central galaxy of the group. The NGC 5044 Group appears clearly defined in redshift space, with a mean heliocentric radial velocity of (νr) = 2461 ± 84km s-1 (z = 0.0082), and a moderate dispersion of σνr = 431 km s-1. Our kinematical data show no luminosity segregation for early-type galaxies: both dwarf and bright E/S0 systems show very similar velocity distributions (σνr ∼290km s-1). This is in contrast to late-type galaxies, which seem to display a broader distribution (σνr ∼680 km s-1).